2015
DOI: 10.1007/s00441-015-2147-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in thestrial blood–labyrinth barrier of aged C57BL/6 mice

Abstract: Tight control over the cochlear blood flow (CoBF) and blood-labyrinth barrier (BLB) in the stria vascularis is critical for maintaining the ionic, fluid, and energy balance necessary for hearing function. Inefficient CoBF and disruption of BLB integrity have long been considered major etiologic factors in a variety of hearing disorders. In this study we investigated structural changes in the BLB of the stria vascularis in age-graded C57BL/6 mice (1 month to 21 months) with a focus on changes in two blood barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 75 publications
4
41
0
Order By: Relevance
“…We recently reported that strial PCs regulate TJ expression between ECs and are essential for intrastrial fluid-blood barrier integrity (Neng et al, 2013a). Strial PCs derived from neonatal day-10~15 mice dramatically promote spouting angiogenesis in an in vitro cell-line-based 3D co-culture, as shown in Figure 6 (Neng et al, 2015). Studies from non-cochlear tissues show that PCs also contribute to BM formation by directly synthesizing type IV collagen, glycosaminoglycan, fibronectin, nidogen-1, perlecan , and laminin (Allt et al, 2001; Fisher, 2009; Shepro et al, 1993), and inhibit the activity of destabilizing matrix metalloproteinases (MMP), such as MMP-2 and MMP-9 (Zozulya et al, 2008).…”
Section: Major Components and Structure Of The Cochlear Intrastriamentioning
confidence: 96%
See 4 more Smart Citations
“…We recently reported that strial PCs regulate TJ expression between ECs and are essential for intrastrial fluid-blood barrier integrity (Neng et al, 2013a). Strial PCs derived from neonatal day-10~15 mice dramatically promote spouting angiogenesis in an in vitro cell-line-based 3D co-culture, as shown in Figure 6 (Neng et al, 2015). Studies from non-cochlear tissues show that PCs also contribute to BM formation by directly synthesizing type IV collagen, glycosaminoglycan, fibronectin, nidogen-1, perlecan , and laminin (Allt et al, 2001; Fisher, 2009; Shepro et al, 1993), and inhibit the activity of destabilizing matrix metalloproteinases (MMP), such as MMP-2 and MMP-9 (Zozulya et al, 2008).…”
Section: Major Components and Structure Of The Cochlear Intrastriamentioning
confidence: 96%
“…A population of around 1220 to 1300 PCs is found in the intrastrial fluid-blood barrier of the normal adult C57/6J mouse cochlea (Neng et al, 2015), as shown in Figure 2A. Extensively branched strial PCs tightly embrace the abluminal strial capillary wall and embed in the BM (Figure 2B).…”
Section: Major Components and Structure Of The Cochlear Intrastriamentioning
confidence: 99%
See 3 more Smart Citations